Pengaruh Parsi terhadap Sastra Sufistik Melayu Islam - Abdul Hadi WM (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2014)
This writing analyzes literary works of Archipelgo, in which the works are sufis in manner and are influenced by Persian tradition. Among those works there are four foremost literatures i.e. Tāj al-Salātṭīn (Crown of Kings), Hikayat Amīr Ḥamzah, Hikayat Muḥammad ‘Alī Ḥanafiyyah, and Hikayat Burung Pingai. In a while, such Persian inspiration can be found in the form of poetry, like rubā‘ī, ghazal, mathnawī and qiṭ‘ah, as discovered within Tāj al-Salātīn and Hikayat Amīr Ḥamzah. In another case, the inspiration relates to the use of symbols of bird (symbol of human soul or spirit) like in Hikayat Burung Pingai, but sometimes such influence is just in aesthetic horizon and paradigm.